2022
DOI: 10.3390/coatings12121835
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Dilution Level on Microstructure and Wear Resistance of Fe-Cr-CV Hardfacing Coatings Deposited by PTA-P

Abstract: Soil preparation tools are subject to severe abrasion. The wear resistance of various industrial components can be improved using the hardfacing technique. The improvement in hardfacing wear resistance depends on the microstructure, i.e., the chemical composition of the alloys, the method of overlay, and the parameters of the selected process. The Plasma Transferred Arc with Powder (PTA-P) welding process is interesting as a hardfacing technique since it promotes very low dilution of the substrate in the coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Currently, although there have been relatively numerous studies focused on optimizing cladding structure and processes to enhance substrate performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders remains relatively limited [8]. Common metallurgical bonding technologies between barrel substrates and claddings include overlay welding [9,10], thermal spraying [11,12], electric spark deposition [13,14], and laser cladding [15][16][17]. The study revealed that by conducting PTA welding on the surface of E32 steel, a surfacemodified cladding consisting of tungsten carbide reinforced cobalt was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, although there have been relatively numerous studies focused on optimizing cladding structure and processes to enhance substrate performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders performance, research on the induction melting cladding process of copper alloys on the inner walls of cylinders remains relatively limited [8]. Common metallurgical bonding technologies between barrel substrates and claddings include overlay welding [9,10], thermal spraying [11,12], electric spark deposition [13,14], and laser cladding [15][16][17]. The study revealed that by conducting PTA welding on the surface of E32 steel, a surfacemodified cladding consisting of tungsten carbide reinforced cobalt was obtained.…”
Section: Introductionmentioning
confidence: 99%